PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE STAD DENGAN SOAL-SOAL PEMECAHAN MASALAH PADA MATA PELAJARAN MATEMATIKA DI SMA NEGERI 6 PALEMBANG - Indriati; Hartono, Yusuf (Mathematics Education Journal, 2011)
The clues of the research is to known description of students problem solving ability by applying of Cooperative STAD type by problem solving . Model of study of cooperative STAD type by problem solving is a model to solve mathematics problem that have done by groups giving clues. The clues consist of some solving keys that given a part, each of member groups get a key. Subject of reseach are 48 students of grade XI natural science in senior high school 6 Palembang. Data collecting have done by giving test that content 3 discription question. The results of analysis shown mean of discriptor indicator are 74.34%, average abilty are 79.04 or 85.42% have shown good ability for problem solving. Conclusions of this reseach are learning use study model of Cooperative Problem Solving could be done to practise the ability of student’s problem.DOI: 10.22342/jpm.5.2.598.